2023
DOI: 10.1098/rsbl.2023.0019
|View full text |Cite
|
Sign up to set email alerts
|

Developmental environments do not affect thermal physiological traits in reptiles: an experimental test and meta-analysis

Abstract: On a global scale, organisms face significant challenges due to climate change and anthropogenic disturbance. In many ectotherms, developmental and physiological processes are sensitive to changes in temperature and resources. Developmental plasticity in thermal physiology may provide adaptive advantages to environmental extremes if early environmental conditions are predictive of late-life environments. Here, we conducted a laboratory experiment to test how developmental temperature and maternal resource inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Fifteen minutes before each performance measure, lizards were placed in an incubator at 28 °C to ensure constant body temperature across lizards. Although recent studies have shown that the thermal optimum is slightly higher than 28 °C ( Anderson et al 2023 ; Zhang et al 2023 ) there is substantial individual and species-specific variation with 28 °C being firmly within this range. Animals were then transferred to the racetrack and were chased down toward a terrarium placed at the end of the track.…”
Section: Methodsmentioning
confidence: 97%
“…Fifteen minutes before each performance measure, lizards were placed in an incubator at 28 °C to ensure constant body temperature across lizards. Although recent studies have shown that the thermal optimum is slightly higher than 28 °C ( Anderson et al 2023 ; Zhang et al 2023 ) there is substantial individual and species-specific variation with 28 °C being firmly within this range. Animals were then transferred to the racetrack and were chased down toward a terrarium placed at the end of the track.…”
Section: Methodsmentioning
confidence: 97%